Liability and Compensation for Damage in Connection with the Carriage of Hazardous and Noxious Substances by Sea under Croatian Law - Ćorić, Dorotea; Tuhtan Grgić, Iva (Transactions on Maritime Science, 2024)
The quantity and volume of hazardous and noxious substances transported by ships as cargo have been increasing markedly. The trend is anticipated to persist and even accelerate in the Adriatic Sea due to the expansion of port infrastructure. Concomitantly with this expansion, the probability of incidents involving these substances, which have the potential to cause significant damage, is also on the rise. At present, the Republic of Croatia lacks the specific legal framework that would provide a comprehensive legal basis for liability, prompt, and adequate compensation for damage to persons and property, liability for clean-up, and reinstatement measure costs, and economic losses resulting from the transportation of such substances by sea. The objective of this paper is to provide an overview of the provisions of Croatian law that regulate liability and compensation in the event of such an accident. The analysis demonstrates the deficiencies of fragmented approach. Moreover, the paper examines the stipulations of the International Convention on Liability and Compensation for Damage in Connection with the Carriage of Hazardous and Noxious Substances by Sea of 2010, and the prospective advantages of its ratification. These include double-tier liability, a special regime of limitation of liability, compulsory insurance of liability and the right to direct action. In consideration of Croatia's maritime and tourist-oriented economy, the authors highlight the country's substantial interest in not only the ratification of the 2010 HNS Convention and paving the way to its entry into force, but also in amendments to the Croatian Maritime Code in that respect.